Malocclusion – Modern Views, Types and Treatment - Abdusalimovna, Kuzieva Madina (American Journal of Bioscience and Clinical Integrity, 2024)
The article provides an overview of modern approaches to the identification and justification of the choice of management tactics for patients with malocclusion and crowding of teeth. Malocclusion is caused by impaired jaw growth or abnormalities in teething. For example, crowding of teeth occurs if permanent teeth are large and erupted on time, and jaw growth has stopped. Sometimes a violation of jaw growth can result in the absence of canines, incisors or premolars, or the appearance of gaps and diastems (gaps between the front teeth).